The NUMBERS of Our Lives. - Miller, Claire Cain (New York Times Book Review)
The article discusses U.S. colleges such as Columbia University that offer courses on Big Data analysis and data science. The social, business, and scientific research purposes of data analysis are discussed, as well as projected salaries for data science graduates. Demand for analysts, curriculum planning, and computer programming courses are also mentioned. INSET: Geek Appeal: New York vs. Seattle.